Online Transportation Law Reform for Justice and Sustainability - Andy Hendarwanto; Naya Amin Zaini; Hono Sejati (Dinasti Research, 2024)
This research discusses the urgent need for legal reform in the regulation of online transportation to create justice and sustainability for all parties involved, especially driver partners and consumers. The current legal vacuum creates significant imbalances in the relationships between application companies and drivers, often leading to exploitation and income uncertainty for drivers. Through an analysis of existing policies and practices, this study identifies the challenges faced by drivers regarding their rights in an unbalanced partnership system, as well as the impacts of fluctuating tariffs and non-transparent profit-sharing. Furthermore, this research explores various efforts needed to update regulations, including the establishment of minimum tariff standards, a fair profit-sharing structure, and guarantees of social protection for drivers. It is hoped that the findings of this research can serve as recommendations for policymakers to formulate more inclusive and sustainable regulations in the online transportation industry.